Assessment of the tolerance to low temperatures of native potatoes (Solanum spp), in simulated conditions in La Molina, to mitigate climate change. - Quintana Palacios, Cristina; Roldán Chávez, Agripina; Jiménez Dávalos, Jorge (Instituto Nacional de Innovación Agraria - INIA, 2018)
Páginas 72-73.